Can Leadership Style Moderating the Role of Ethos Work and Career Development in Affect Performance - Nugroho Sudarsono, Wisnu Whendy; Gunadi Rusydi, Dheo Rimbano, M Yusuf, Sutanta, Noorhamid Ustadi, Benni Mardiyansah, and Jemmy Amin G (Adpebi Science Series, 2022)
This study aims to find out how role ethos work and development career in affect performance employee during the pandemic period (2019-2022) with style leadership as variable moderation. The type of research used in this study is a quantitative type, with a total sample of 43 ASN at BPKAD Lubuklinggau City. as respondents and using data analysis techniques moderated regression analysis (MRA). The results showed that during the pandemic (2019-2022) work ethic and career development together have a significant role to play can affect the performance of the Lubuklinggau BPKAD. However, the career development variable partially does not have a significant role in influencing performance and the leadership style variable is not able to be a moderating variable, in other words, leadership style during the pandemic (2019-2022) does not have a significant role in strengthening or weakening work ethic and career development to influence performance.